An implementation of the conjugate gradient method for cadastral survey adjustment [microfilm] ... [et al.] - 191948 Abdullah Daud; Razali Ismail, 1960-; Shuhana Shamsuddin; Yusof Munajat (Skudai : Universiti Teknologi Malaysia, 1997)
Thesis (Doctor of Philosophy) - Universiti Teknologi Malaysia, 1997